2006
DOI: 10.1002/ijc.22409
|View full text |Cite
|
Sign up to set email alerts
|

The 6‐maleimidocaproyl hydrazone derivative of doxorubicin (DOXO‐EMCH) is superior to free doxorubicin with respect to cardiotoxicity and mitochondrial damage

Abstract: Doxorubicin causes a chronic cardiomyopathy in which genetic and functional lesions of mitochondria accumulate in the longterm and explain in part the delayed onset of heart dysfunction. DOXO-EMCH a 6-maleimidocaproyl hydrazone derivative of doxorubicin, is an albumin binding prodrug which has entered clinical trials because of its superior antitumor and toxicological profile. In the present work, we examined the chronic cardiotoxicity of DOXO-EMCH in direct comparison with doxorubicin. Rats (11 weeks of age) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 28 publications
(46 reference statements)
1
42
0
1
Order By: Relevance
“…In contrast, doxorubicin administered at 4.0 and 8.0 mg/kg, using the same schedule and route of injection as INNO-206, resulted in deaths in all animals by day 42. Other laboratories have shown that INNO-206 is superior to doxorubicin with respect to reducing cardiotoxicity and mitochondrial damage at equimolar as well as equitoxic doses in a rat model (42), and significantly lower levels of INNO-206 were observed in the heart, liver, and kidneys of mice when compared with similar studies assessing doxorubicin (21). The lack of deaths observed in our in vivo study with INNO-206 is consistent with a favorable shift in the lethal dose, which is 2-to 5-fold higher for INNO-206 compared with free doxorubicin (37,43).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, doxorubicin administered at 4.0 and 8.0 mg/kg, using the same schedule and route of injection as INNO-206, resulted in deaths in all animals by day 42. Other laboratories have shown that INNO-206 is superior to doxorubicin with respect to reducing cardiotoxicity and mitochondrial damage at equimolar as well as equitoxic doses in a rat model (42), and significantly lower levels of INNO-206 were observed in the heart, liver, and kidneys of mice when compared with similar studies assessing doxorubicin (21). The lack of deaths observed in our in vivo study with INNO-206 is consistent with a favorable shift in the lethal dose, which is 2-to 5-fold higher for INNO-206 compared with free doxorubicin (37,43).…”
Section: Discussionmentioning
confidence: 96%
“…INNO-206 was selected as the investigational product for clinical evaluation after toxicology studies in mice, rats, and dogs had shown a two-to fivefold increase in the maximum tolerated dose (MTD) when compared to conventional doxorubicin and a better tolerability in a four-cycle study in rats and a two-cycle study in dogs even at a threefold higher dose for INNO-206 than for doxorubicin [14]. INNO-206 has also shown significantly less chronic cardiotoxicity at equimolar as well as equitoxic doses compared to doxorubicin in a rat model [15].…”
Section: Introductionmentioning
confidence: 95%
“…3) [46,47]. Due to its maleimide group DOXO-EMCH binds quantitatively and selectively to the cysteine-34 position of albumin after intravenous administration.…”
Section: Mitochondrial Lesions In Human Heartsmentioning
confidence: 99%